GAME EDUKATIF SEBAGAI UPAYA MENGATASI KESULITAN BELAJAR BAHASA ARAB KELAS RENDAH - Ayok Ariyanto (Universitas Muhammadiyah Ponorogo, 2017)
It has become a common culture that learners often have difficulty in understanding the subject matter. arabic language is considered a scourge that is daunting and very difficult to understand. It became one of the sockets of the 90s to learners why they become lazy and reluctant to focus when dealing with the eyes of the Arab Language. It's no wonder a lot of values among learners are insufficient or still under the minimum total criterion set by the school. Then the Educational Gaming method is considered capable of providing solutions to the problems experienced by a student, that is because of that kid, in general, are very fond of all kinds of game. In this method can also provide an opportunity for parts can learn while playing which is a trait typical of a child. It can make learning to be more meaningful since learners are stimulated to develop their creativity, the ability to think, as well as their imagination.